2014
DOI: 10.1002/ejic.201402110
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Crystallization Strategy for Metastable h‐MoO3 Crystals with Polyvinylpyrrolidone Induction

Abstract: Micro‐sized hexagonal‐phase MoO3 (h‐MoO3) crystals were successfully prepared by a polyvinylpyrrolidone (PVP) induced aqueous route with (NH4)6Mo7O24·4H2O and HCl as raw materials. The linear structure of the PVP molecules matches the tunnel structure of the metastable h‐MoO3 crystals and, thus, enables the induced crystallization in an aqueous solution even at near‐ambient temperatures (40–50 °C). The achieved h‐MoO3 crystals have good monodispersity with a one‐dimensional (1D) outline and hexagonal cross‐sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
(23 reference statements)
2
4
0
Order By: Relevance
“…46 Guo et al showed that ATM (pSer-1981) and Chk1 (pSer-345) activations were concomitant with cucurbitacin B induced G 2 /M arrest in human lung adenocarcinoma epithelial A549 cells, but they did not observe ATR (pSer-428) and Chk2 (pThr-68) activations. 47 In our study, a significant increase of the phosphorylation of Chk1 on Ser-345 after DEB exposure was observed, whereas the phosphorylation of Chk2 on Thr-68 was not affected, which is consistent with the result of a previous study. 47 We also found that the increased expression of phosphorylates Cdc25c and Cdc2, which are downstream factors of the Chk1 signal cascade, in response to DNA damage.…”
Section: ■ Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…46 Guo et al showed that ATM (pSer-1981) and Chk1 (pSer-345) activations were concomitant with cucurbitacin B induced G 2 /M arrest in human lung adenocarcinoma epithelial A549 cells, but they did not observe ATR (pSer-428) and Chk2 (pThr-68) activations. 47 In our study, a significant increase of the phosphorylation of Chk1 on Ser-345 after DEB exposure was observed, whereas the phosphorylation of Chk2 on Thr-68 was not affected, which is consistent with the result of a previous study. 47 We also found that the increased expression of phosphorylates Cdc25c and Cdc2, which are downstream factors of the Chk1 signal cascade, in response to DNA damage.…”
Section: ■ Discussionsupporting
confidence: 94%
“…47 In our study, a significant increase of the phosphorylation of Chk1 on Ser-345 after DEB exposure was observed, whereas the phosphorylation of Chk2 on Thr-68 was not affected, which is consistent with the result of a previous study. 47 We also found that the increased expression of phosphorylates Cdc25c and Cdc2, which are downstream factors of the Chk1 signal cascade, in response to DNA damage. To establish the role of Chk1 in DEB-mediated G 2 phase arrest in GC-2 cells, Chk1 siRNA was transfected to knock down Chk1 gene expression, which efficiently reversed downstream effectors such as pCdc25c (Ser 216) and p-Cdc2 (Tyr 15).…”
Section: ■ Discussionsupporting
confidence: 94%
“…[28][29][30] Research work have indicated that molybdenum oxide (MoO 3 ) has various forms: one of them is the thermodynamic and stable phase of orthorhombic α-MoO 3 , [11][12][13] and the others are metastable phases of monoclinic β-MoO 3 , [31] hexagonal h-MoO 3 . [32,33] The conversion of the stoichiometric MoO 3 into nonstoichiometric oxygen deficiency molybdenum oxide (MoO 3-x ) since that the becoming of heterovalent heteroatoms or lattice vacancies or lattice vacancies [34,35] have excellent advantages, such as electrical conductivity, catalytic properties, optical properties and so on, to be achieved by controlling and adjusting the valence state of molybdenum element [36,37] which will be applied in various science fields. Furthermore, increased with oxygen hole, the color of MoO 3-x arrange from blank to obvious blue with an valid LSPR absorption in NIR.…”
Section: Introdutionmentioning
confidence: 99%
“…[ 186 ] This is because tunnel and layered structures in metastable MoO 3 are generally more spacious in the crystal structure and this contributes to accelerated electron–hole migration under UV irradiation. [ 187 ] Tunnel structures present in metastable MoO 3 also allow more ions to intercalate, which promotes efficient ion insertion/extraction and reduces potential barriers for ion diffusion, [ 188 ] which is regarded as an improved photochromic activity compared to the orthorhombic α‐MoO 3 . For example, h‐MoO 3 and α‐MoO 3 films fabricated using ion exchange and chemical deposition exhibit fluorescence emission peaks at 440 and 630 nm (h‐MoO 3 ) and at 440 nm (α‐MoO 3 ).…”
Section: Photochromic Applications Of Oxides and Hybrid Materials In Uv Sensingmentioning
confidence: 99%